Qualitative methods in the characterization of legal documents - Torres, Simone; Almeida, Maurício Barcellos (Qualitative and Quantitative Methods in Libraries, 2017)
This paper describes scientific research developed in the scope of Information Science, and uses qualitative methods to address the issue of identifying what would grant a document its own legal characterization. The research methodology employs qualitative methods which are organized in two main stages, namely, bibliographical research and documentary research. As a result, a general manner to characterize legal documents was found based on six categories, which include the typology of documents encompassed in the research. It was concluded that legal documents are instruments able to regulate social aspects of life, establish rules of behavior in society, discipline the actions of public administration, resolve legal issues, develop business between people and companies, record natural and social facts of legal relevance and, additionally, record, accumulate, share and preserve theoretical legal knowledge.